Clinical value of KiSS-1 and MMP-2 expression levels in breast cancer tissue in evaluating prognosis of elderly breast cancer patients after modified radical mastectomy: KiSS-1 and MMP-2 expression in breast cancer - Lv, Jiyang; Zhang, Junya; Wu, Fangfang (Cellular and Molecular Biology, 2024)
We attempted to clarify clinical value of KiSS-1 and MMP-2 levels in breast cancer (BC) tissue in evaluating prognosis of elderly BC patients after modified radical mastectomy (MCM). The data of 192 elderly female BC patients receiving MCM in our hospital from January 2018 to December 2022 were collected. According to prognosis, patients received division into poor prognosis group (n = 43) and good prognosis group (n = 149). The serum CEA level and KiSS-1 and MMP-2 levels in BC tissue received measurement in both groups. The predictive value of KiSS-1 and MMP-2 alone and jointly in adverse prognosis of elderly BC patients after MCM received assessment. Results showed that No statistical significance was exhibited between both groups in general data (P > 0.05). The serum CEA level and MMP-2 expression in BC tissue in poor prognosis group exhibited elevation relative to those in good prognosis group, and KiSS-1 expression in BC tissue in poor prognosis group exhibited depletion relative to that in good prognosis group, indicating statistical significance (P < 0.05). The high-level KiSS-1 might be a protective element for adverse prognosis of elderly BC patients after MCM, and high-level CEA and MMP-2 might be an independent risk element for adverse prognosis of elderly BC patients after MCM (P < 0.05). KiSS-1 and MMP-2 alone and jointly predicted AUC of adverse prognosis in elderly BC patients after MCM were 0.93, 0.802 and 0.958, with certain predictive values; when cutoff values of KiSS-1 and MMP-2 were 6.15 and 2.26, the predictive value was the best. In conclusion, KiSS-1 and MMP-2 levels in BC tissue possess relation to adverse prognosis of MCM. KiSS-1 and MMP-2 levels in elderly BC patients before surgery may be detected in the future to assist in prognosis evaluation of elderly BC patients after MCM.